2009
DOI: 10.3354/meps08304
|View full text |Cite
|
Sign up to set email alerts
|

Damage and disturbance to coral and sponge habitat of the Aleutian Archipelago

Abstract: Video imagery was examined to quantify seafloor disturbance and damage to corals and sponges relative to fishing practices in the central Aleutian Islands of Alaska. Corals and sponges were classified as damaged if they had broken skeletons, missing or broken branches, were torn (i.e. sponges) or detached from the seafloor, or were attached but lying on the seafloor. Disturbance was defined as any alteration to the seafloor or biota caused by fishing gear or natural events. Overall, 14% of corals and 21% of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 8 publications
2
31
0
Order By: Relevance
“…Anti patharians, hydrocorals, demosponges, and hexactinellid sponges had the highest proportions of damaged individuals, particularly at depths shallower than 1000 m, indicating that they have little resistance to physical disturbance. The percentages of damaged corals and sponges reported here are considerably lower than the proportions previously reported for a subset of these data (14% and 21%, respectively) by Heifetz et al (2009), but the values presented here for damaged corals (6.5% overall and 7.9% for corals seen at depths <1000 m) are consistent with the damage rate (8.5%) previously reported from the region (Stone, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Anti patharians, hydrocorals, demosponges, and hexactinellid sponges had the highest proportions of damaged individuals, particularly at depths shallower than 1000 m, indicating that they have little resistance to physical disturbance. The percentages of damaged corals and sponges reported here are considerably lower than the proportions previously reported for a subset of these data (14% and 21%, respectively) by Heifetz et al (2009), but the values presented here for damaged corals (6.5% overall and 7.9% for corals seen at depths <1000 m) are consistent with the damage rate (8.5%) previously reported from the region (Stone, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Damage observed to corals and sponges on transects was previously reported for a subset of the data presented here (Heifetz et al, 2009). That report indicated that 14% of corals and 21% of sponges overall were damaged and that disturbance to the seafloor from fishing gear was widespread and evident on most transects.…”
Section: Damaged Corals and Spongessupporting
confidence: 77%
See 1 more Smart Citation
“…Second, smaller epifauna may escape destruction by trawling. Third, damage may reduce the size of these structures: Primnoa pacifica can lose most of their branches after a single trawl tow (Krieger 2001) and both corals and sponges show damage in high-intensity trawled areas (Heifetz et al 2009). A fourth possibility is recent recolonisation, as observed in the Gulf of Alaska for P. pacifica (Krieger 2001).…”
Section: Effects Of Trawlingmentioning
confidence: 99%
“…trawling gear (Heifetz et al 2009). Their recovery from trawling activity may be so slow (Andrews et al 2002, Risk et al 2002) that these biogenic habitats should be viewed as a nonrenewable feature.…”
Section: Introductionmentioning
confidence: 99%